Identifying the effects of government spending shocks with and without expected reversal: An approach based on U.S. real-time data - Jacopo Cimadomo; Sebastian Hauptmeier; Sergio Sola (Graduate Institute of International and Development Studies, 2011)
This paper investigates how expectations about future government spending affect the transmission of fiscal policy shocks. We study the effects of two different types of government spending shocks in the United States: (i) spending shocks that are accompanied by an expected reversal of public spending growth below trend; (ii) spending shocks that are accompanied by expectations of future spending growth above trend. We use the Ramey (2011)'s time series of military build-ups to measure exogenous spending shocks, and deviations of forecasts of public spending with respect to past trends, evaluated in real-time, to distinguish shocks into these two categories. Based on a structural VAR analysis, our results suggest that shocks associated with an expected spending reversal exert expansionary effects on the economy and accelerate the correction of the initial increase in public debt. Shocks associated with expected spending growth above trend, instead, are characterized by a contraction in aggregate demand and a more persistent increase in public debt. The main channel of transmission seems to run through agents' perception of the future macroeconomic environment.
Keywords: E62; E65; H20; 330; Government spending shocks; Survey of professional forecasters; Real-time data; Spending reversal; Fiscal multipliers; Öffentliche Ausgaben; Schock; Prognoseverfahren; Finanzpolitik; Multiplikator; USA